Single-Phase Bi-directional Ćuk Inverter for Battery Applications - Shelembe, Lindani (Department of Electrical Engineering, 2020)
Bidirectional inverters are widely applied in photovoltaic and wind systems that require battery power backup. They are advantageous over unidirectional inverters because of their ability to convert DC power into AC power and then AC power back into DC power to recharge for storage purposes. Generally, bidirectional inverters are designed to have multiple power stages and/or make use of transformers for isolation and voltage/current gain. This usually increases the cost of production and oftentimes reduces the efficiency of the system. At the same time, attempts at eliminating usage of transformers and reduction in the number of power stages limits the range of bidirectional inverters’ capabilities. This is because battery applications today require low voltage DC-AC inverters with AC-DC power flow capability to store energy for later use. As such, only buck-boost based topologies are majorly being proposed and used for this functionality. The buck boost converter is the most widely used in such applications because of its higher efficiency, low component count and simple structure. It has drawbacks, however, such as: pulsating input and output currents - this leads to lower high electromagnetic interference; lower power factor during AC-DC power flow rectification when the batteries are being recharged; and external filter is also required during this power flow to keep the charging voltage constant. This research proposes a bidirectional inverter that attempts to overcome the drawbacks of the widely used buck-boost converter-based topology. The bidirectional inverter proposed in this work is based on a bidirectional Ćuk converter. The Ćuk converter has both continuous input and output currents. A galvanic isolation option on a Ćuk converter is simpler than a buck boost converter - this is important for grid tied systems. The inverter is based on a pseudo DC-link architecture - it uses a front end Ćuk converter cascaded with an unfolding bridge to convert DC power into AC power. The switches in the converter stage are switched at high frequency, while the switches in the unfolding stage are switched slower at the grid frequency. This configuration is desirable over the two-stage topologies because the switching losses in the unfolding bridge are lower because of this low switching frequency used. This configuration also ensures good switch utilization at the unfolding stage by lowering the parasitic effects on the power transfer. The proposed inverter has 4 modes of operation: during modes I and II the power is positive, and it converts DC power into AC power; during modes III and IV the power is negative, and it converts AC power back into DC power. The inverter is designed such that during DC-AC power flow, the input and output inductor currents and coupling capacitor voltage are continuous for improved efficiency. During the AC-DC power flow, the coupling capacitor voltage is discontinuous to achieve a higher input power factor by improving the AC line current, thereby simultaneously increasing the efficiency. The inverter was analysed in terms of: the dead time inserted into the switches to avoid shoot through and shortcircuiting switches; the parasitic effects on the power transfer ratio. Because the Cúk inverter is a high order system, several robust control strategies, such as sliding mode and current control have been proposed. These control methods require complex theory and present practical challenges to be reviewed. As such a new nested loop control strategy was proposed based on the dynamics of the coupling capacitor as the primary energy storage in the Cúk inverter. The control strategy uses 2 loops: an inner current loop and an outer voltage loop. Lead compensators were designed for both the current and voltage loops to achieve good dynamic response at a high bandwidth. Both simulated and experimental results showed that the bidirectional inverter was able to meet the design specifications. The control strategy showed good dynamic response and disturbance rejection under several inverter variations. Although the efficiency during simulations was above 96%, the experimental efficiency dropped significantly because the inverter was built on a Vero board for easy manipulation. The AC input power factor was > 0.95 for both simulated and experimental results.